Inter-district variation and convergence in agricultural productivity in India - Mohd Murtaza; Tariq Masood (Agricultural Economics Research Review, 2023)
Using district-level data for the 1971–2010 period, we examine the convergence in agricultural productivity. We find significant spatial variation in agricultural productivity and growth in the past four decades at different levels of spatial aggregation, and we find evidence of both absolute and conditional convergence. The state-wise convergence suggests that the districts of most states are converging towards the steady-state. At the regional level there is strong convergence for all the four regions. Conditional convergence suggests that districts with better initial conditions are growing at a higher rate.